Resonant (P+RES) controller applied to voltage source inverter with minimum DC link capacitor - Gazoli, Jonas Rafael; De Oliveira F., Milton Evangelista; Espíndola, Marcos Fernando; De Siqueira, Thais Gama; Villalva, Marcelo Gradella [UNESP]; Ruppert, Ernesto (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Voltage source inverters use large electrolytic capacitors in order to decouple the energy between the utility and the load, keeping the DC link voltage constant. Decreasing the capacitance reduces the distortion in the inverter input current but this also affects the load with low-order harmonics and generate disturbances at the input voltage. This paper applies the P+RES controller to solve the challenge of regulating the output current by means of controlling the magnitude of the current space vector, keeping it constant thus rejecting harmonic disturbances that would otherwise propagate to the load. This work presents a discussion of the switching and control strategy. © 2011 IEEE.
Keywords: current control; p+res; reduced dc link capacitor; resonant controller; space vector; voltage source inverter; Control strategies; Dc link capacitor; DC-link voltages; Harmonic disturbances; Input current; Input voltages; Low order harmonics; Output current; Resonant controller; Space Vector; DC power transmission; Electric current control; Electrolytic capacitors; Power electronics; Vector spaces; Controllers